Marguerite Porete e Mestre Eckhart : o aniquilamento e o desprendimento como caminhos para uma ética do amor - Melo, Valkíria Oliveira de (2019)
The present paper presents the mystical thinking developed by Marguerite Porete and Master Eckhart, which aims at the transformation of the soul after the mystical experience with Love/God, at which time the soul receives the understanding of Love/God. The annihilated/detached soul returns from the encounter with God (which is Love itself), transformed by God/Love in Love, with another perception of the world and people, so that its action after the encounter with the Divine is guided by its Love. The soul that has been transformed into love, being in the world, becomes a reflection of God, a moment that perceives and moves in relation to another with Love (its new nature), to this action of the soul transformed by love, we call it, in our work, from 'Ethics of Love'. To reach this state of soul elevation and understanding of God/Love, Marguerite Porete and Master Eckhart suggest, respectively, in their writings, The Mirror of the simple and annihilated souls that remain only in the will and desire of Love and in the Germans Sermons and in The Book of Divine Consolation, the path to the annihilation and detachment of both external (world) and internal (will/self) things. In this sense, the aim of this paper is to present the path of annihilation and detachment that Marguerite and Eckhart propose to support the reader about the mystical thought of our authors, enabling the understanding of the moment when the soul, when losing its will, becoming nothing, it can have an intellectual experience about God/Love and, from that understanding, be transformed and transforming its relationship with its neighbor, what we call the 'Ethics of Love'.